Atomistica.online - web application for generating input files for ORCA molecular modelling package made with the Anvil platform - Armaković, Stevan; Armaković, Sanja J. (Molecular simulation, 2023)
We present the atomistica.online, a web application for generating input files for the ORCA molecular modelling package. atomistica.online is entirely made with the Anvil platform, which allows the development of web applications using only Python programming language. ORCA is one of the most, if not the most, powerful molecular modelling tools covering a wide range of possibilities for atomistic calculations on molecules. Speed, ease of installation and use, and clear and intuitive syntax for input files are some of ORCA's characteristics that make it one of the most cited modelling tools in the last several years. Nevertheless, although tools for generating input files for ORCA exist, they are not available as online applications. In this work, we demonstrate how the combination of Python programming language and the Anvil platform makes the development of scientific web applications available to all scientists. All tools within atomistica.online are freely available at the project's official website - https://atomistica.online